40Ar-39Ar analyses of Y-74063 and ALH-78230: Consortium study onunique meteorites from Antarctica - Kaneoka, Ichiro; Takaoka, Nobuo; Yanai, Keizo (National Institute of Polar Research, 1992)
P(論文) As part of a consortium study on unique meteorites from Antarctica, ^<40>Ar-^<39>Ar analyses were performed for two meteorites Y-74063 and ALH-78230,which are related to lodranite and the Acapulco meteorite. Y-74063,93 shows an ^<40>Ar-^<39>Ar plateau age of 4556±53 Ma, containing about 10^<-6>cm^3STP/g trapped ^<36>Ar. ALH-78230,55 also indicates an ^<40>Ar-^<39>Ar plateau age of 4531±23 Ma in the higher temperature fractions, but the lower temperature fractions suggest the occurrence of a later degassing event around 400-500 Ma. Trapped ^<36>Ar is about 10^<-8>cm^3STP/g. These results indicate that the two meteorites Y-74063 and ALH-78230 experienced different thermal histories. departmental bulletin paper